143k views
4 votes
-5x - 5y + 4x - (2y + 3)

2 Answers

4 votes

Answer:

-x-7y-3

Explanation:

distribute parentheses:

-(2y)-(3)= -2y-3

= -5x-5y+4x-2y-3

simplify

group like terms= -5x+4x-5y-2y-3

add similar elements= -x-5y-2y-3

add similar elements= -x-7y-3

Therefore, simplest expression is -x-7y-3

I hope this helps!!!

User Mirkokiefer
by
4.9k points
5 votes

Explanation:

-5x - 5y + 4x - (2y + 3)

= - 5x + 4x - 5y - (2y + 3)

= - x - 5y - 2y - 3

= - x - 7y - 3 ( Answer )

User Kamyar Gilak
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.